2021
DOI: 10.3390/app11052128
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Galvanostatic Anodic Polarization to Accelerate the Corrosion of the Bioresorbable Magnesium Alloy WE43

Abstract: In the field of surgery, bioresorbable magnesium is considered a promising candidate. Its low corrosion resistance, which is disadvantageous for technical application, is advantageous for surgery since the implant fully degrades in the presence of the water-based body fluids, and after a defined time the regenerating bone takes over its function again. Therefore, knowledge of the corrosion behavior over several months is essential. For this reason, an in vitro short-time testing method is developed to accelera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Thus, the performed experiments confirmed that it is possible to control the dissolution rate through galvanostatic polarization. The linear relationship between immersion time and hydrogen volume for constant current densities as well as the relationship between increasing current density and increasing HER agree with the literature [24,26] and could also be demonstrated in our own preliminary work on embedded samples [31]. The lower HER for the PEO specimens shows that the qualitative dissolution behavior of this second variant can be controlled by this test strategy.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Thus, the performed experiments confirmed that it is possible to control the dissolution rate through galvanostatic polarization. The linear relationship between immersion time and hydrogen volume for constant current densities as well as the relationship between increasing current density and increasing HER agree with the literature [24,26] and could also be demonstrated in our own preliminary work on embedded samples [31]. The lower HER for the PEO specimens shows that the qualitative dissolution behavior of this second variant can be controlled by this test strategy.…”
Section: Discussionsupporting
confidence: 89%
“…The starting point was an experimentally determined mathematical relationship (Equation ( 6)) between the dissolution rate . m diss and the galvanostatic current density i [31]. This relationship was determined on embedded samples and can be assumed to be a two-dimensional (2D) case.…”
Section: Corrosion Investigationsmentioning
confidence: 99%
See 2 more Smart Citations